Characteristics and Risk Analysis of Tuberculosis (TB) Cases at The Paal V Community Health Centre in Jambi City - Sarah Dhiba Naibaho; Ermi Girsang; Irza Haicha Pratama (Universitas Pahlawan Tuanku Tambusai, 2026)
Tuberculosis (TB) remains a major global public health threat, with Indonesia ranking second worldwide in new cases at 759,000. Puskesmas Paal V in Jambi City recorded 312 cases in 2023 with a treatment success rate of 85.6 percent, still below the National Tuberculosis Control Program target of 90 percent. This study aimed to analyze the characteristics and risk factors of TB occurrence at Puskesmas Paal V during the period January 2023 to April 2026 using multivariate logistic regression integrated with GIS-based spatial mapping. A retrospective cohort design was applied to 285 microbiologically confirmed pulmonary TB patients, selected through total sampling. Data from the e-TB Manager register, medical records, and validated questionnaires were analyzed using Chi-Square tests, logistic regression, and spatial analysis including Moran's I and Getis-Ord Gi*, processed through SPSS 26.0 and QGIS 3.28. Cases were dominated by males (65.6 percent) and the 25 to 44 year age group (57.5 percent), with 69.1 percent presenting at an advanced stage. Significant risk factors included household contact history (AOR 4.31), smoking behavior (AOR 3.14), housing density (AOR 2.45), Diabetes Mellitus (AOR 2.61), and malnutrition (AOR 2.08), collectively explaining 45.2 percent of the variability in TB occurrence. Spatial analysis identified three clustered hotspots (Moran's I 0.45), underscoring the importance of area-based intervention alongside individual risk factors.